Analisis Pertanggungjawaban Laporan Keuangan Organisasi Nirlaba (Studi Kasus Pada HMJ FEB Untan) - Rafa, Wukuf Dilvan B1031141051 (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2018)
ABSTRACTThe purpose of this study is to determine the suitability of the Department Student Association in implementing financial report making in accordance with the standards of nonprofit organizations. The components of the financial statements are analyzed such as (1) financial position report (2) activity report (3) cash flow report (4) notes on financial statements.Data analysis techniques using Reduction, means to collect the financial statements of the student association to be Presented of data in the form of narrative text then after the reduction and presentation of the data is carried out by drawing conclusions from the results of the study.The results of this study indicate that (1) the four components in the financial statements of the Accounting Student Association (HIMASI) of the Faculty of Economics and Business (FEB) of Tanjungpura University are in accordance with the Statement of Financial Accounting Standards (PSAK) No. 45 (2) the suitability level of the financial statements analyzed reached 77.94% and was categorized according to the standards of non-profit organizations (3) the lack of education and understanding of the application of financial reporting standards for nonprofit organizations is an obstacle in the process of making nonprofit financial statements.Keywords: Department Student Association, Nonprofit Organization, Financial Report, Statement of Financial Accounting Standards (PSAK)Daftar PustakaAlmansharu, Djunaidi Ghony & Fauzan. (2014). Metodologi penelitian kualitatif. Jogjakarta: Ar-Ruzz Media.Andarsari, Pipit Rosita. (2016). Laporan Keuangan Organisasi Nirlaba (Lembaga Masjid). STMIK ASIA Malang. Jurnal Ekonomi Universitas Kadiri. Volume. 1 No. 2. September 2016: 143 â€“ 152.Andi Marlinah., dan Ali Ibrahim. (2018). Penerapan Laporan Keuangan Organisasi Nirlaba Berdasarkan PSAK No. 45 (Studi Masjid Al-Markaz Al-Islami Jenderal M. Jusuf. Jurnal Ilmiah AKMEN Sekolah Ilmu Ekonomi Nobel Indonesia Volume 15 No. 1. Maret 2018Beams, A. Floyd. 2011. Advance Accounting. London : Pearson Education. Diakses dari : http://boomstem.org, tanggal : 27 Mei 2018Effendi Rizal. 2013. Accounting Principles â€˜â€™Prinsip-prinsip Akuntansi Berbasis SAK ETAPâ€. Edisi Revisi Jakarta : PT. Rajagrafindo PersadaEmzir. (2010). Metodologi Penelitian Pendidikan: kuantitatif dan kualitatif. Jakarta: Rajawali pers.Fahmi, Irham, 2011, Analisa Laporan Keuangan, Bandung: Alfabeta.Hadari Nawawi. (2007). Metode Penelitian Bidang Sosial. (Cetakan ke-12). Yogyakarta: Gadjah Mada University Press.Herdiansyah, Haris. (2013). Wawancara, Observasi, dan Focus Groups: Sebagai Instrumen Penggalian Data Kualitatif. PT RajaGrafindo Persada. Jakarta.Hidayati, Irma. (2012). Akuntansi Organisasi Nirlaba: â€œSesuai PSAK No. 45 atau Tidak?â€ (Studi Kasus Pada Ponpes Roudlotul Mubtadiin Balekambang Gemiring Lor Nalumsari Jepara). Skripsi. Sekolah Tinggi Ilmu Ekonomi Nahdlatul Ulama Jepara. Jawa Tegah.Ikatan Akuntan Indonesia (2010) Standar Akuntansi Keuangan No.45 Revisi 2010 Jakarta: Ikatan Akuntan IndonesiaIrsad, Jamil. (2017). Penerapan PSAK Nomor 45 Tentang Pelaporan Keuang Entitas Nirlaba Pada Masjid Besar Nikmatullah Sungai Pinyuh. Skripsi. Universitas Tanjungpura. Pontianak.Kasmir. 2016. Analisis Laporan Keuangan. Jakarta: Raja Grafindo PersadaKieso, Donald E. Jerry J.Weygandt, Paul D. Kimmel. 2014. Accounting Principles Pengantar Akuntansi Edisi 7 Jilid 1. Jakarta: Salemba Empat.Mamesah, Melisa. (2013). Penerapan PSAK No.45 pada GMIM EfrataÂ  Sentrum Sonder Kaitannya dengan Kualitas Informasi Laporan Keungan. Universitas Sam Ratulangi Manado. Jurnal EMBA Volume 1 No.4 Desember 2013. ISSN 2303-1174.Pahala Nainggolan. (2005). Akuntansi Keuangan Yayasan dan Lembaga Nirlaba Sejenis. Jakarta: PT RajaGrafindo Persada.Amaliah, S.A. (2016).Pratama, Ardian. (2017). Analisis Penerapan PSAK Nomor 45 Tentang Pelaporan Keuangan Entitas Nirlaba Bagi Masjid Al-Muhtadin Universitas Tanjungpura. Skripsi. Universitas Tanjungpura. Pontianak.Rizky, Diyani Ade. (2013). Analisis Penerapan PSAK No 45 Pada Yayasan Masjid Al Falah Surabaya. Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya. Jurnal Ilmu & Riset Akuntansi Vol. 2 No. 7.Rudianto. (2008). Pengantar Akuntansi. Jakarta:PT Erlangga.Sri Sapto Bimo Haryana, 2009, Sistem Pengukuran Kinerja Organisasi Nirlaba Pada Masa Krisis Ekonomi (Perbandingan Antara Balance Scorecard Dengan Malcokm Baldridge Criteriaâ€. Diperoleh 31 Juni 2018. http://beemo.blogspot.com/2009/07/sistem-pengukuran-kinerja-organisasi.htmlSugiyono. (2009). Metode Penelitian Bisnis (Pendekatan Kuantitatif, Kualitatif, dan R&D). Bandung: Alfabeta.Umar, H., (2013) Metode Penelitian Untuk Skripsi dan Tesis Bisnis , Jakarta : Raja Grafindo PersadaUmi Muawanah dkk. (2008). Konsep Dasar Akuntansi dan Pelaporan Keuangan untuk Sekolah Menengah Kejuruan. Jakarta: Direktorat Pembinaan Sekolah Menengah KejuruanWulandari, Fresisca. (2015). Penerapan PSAK 45 Dalam Mengkomunikasikan Aktivitas Pelayanan Masjid Al-Falah Surabaya Terhadap Publik. Universitas Surabaya. Calyptra: Jurnal Ilmiah Mahasiswa Universitas Surabaya Vol.4 No.1 (2015)._______________________. (2014). Salinan Keputusan Menteri Nomor 155 /U/1998 tentang Pedoman Umum Organisasi Kemahasiswaan di Perguruan Tinggi (Online). http://bpsenat-binus.forumotion.com/-sk-mendikti--dasar-hukum- bem-ukm-hmj, diakses pada tanggal 15 Maret 2018).